2019
DOI: 10.1038/s41467-019-09593-0
|View full text |Cite
|
Sign up to set email alerts
|

A calcium/cAMP signaling loop at the ORAI1 mouth drives channel inactivation to shape NFAT induction

Abstract: ORAI1 constitutes the store-operated Ca 2+ release-activated Ca 2+ (CRAC) channel crucial for life. Whereas ORAI1 activation by Ca 2+ -sensing STIM proteins is known, still obscure is how ORAI1 is turned off through Ca 2+ -dependent inactivation (CDI), protecting against Ca 2+ toxicity. Here we identify a spatially-restricted Ca 2+ /cAMP signaling crosstalk critical for medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
133
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(148 citation statements)
references
References 55 publications
15
133
0
Order By: Relevance
“…; Zhang et al . ). Both RyRs and IP 3 Rs are activated by Ca 2+ in a bell shaped manner (Bootman & Berridge, ; Berridge et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Zhang et al . ). Both RyRs and IP 3 Rs are activated by Ca 2+ in a bell shaped manner (Bootman & Berridge, ; Berridge et al .…”
Section: Discussionmentioning
confidence: 97%
“…A rapid onset event of high amplitude may be needed to sensitize Ca 2+ release sites to respond to CICR as the Ca 2+ wave begins to propagate (Takamatsu & Wier, 1990;Yao & Parker, 1994;sneyd et al 1995;ZhuGe et al 1999;Niggli & Shirokova, 2007;McCarron et al 2010;Drumm et al 2015). The observation that Ca 2+ waves failed to propagate past each other upon collision suggests that a refractory period follows Ca 2+ transients, possibly due to the need for store reloading or Ca 2+ -induced inactivation of Ca 2+ release channels (Berridge, 2009) or possibly Ca 2+ -induced inactivation of Orai channels (Lee et al 2009;Mullins et al 2009;Zhang et al 2019). Both RyRs and IP 3 Rs are activated by Ca 2+ in a bell shaped manner (Bootman & Berridge, 1995;Berridge et al 1999;Bootman et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The Orai1 and AC8 expression normalized to the β-actin content indicates that Orai1 expression was 371 ± 12 and 393 ± 22% of that in MCF10A cells in MCF7 and MDA-MB-231 cells, respectively, while the AC8 expression was 611 ± 75 and 621 ± 98% of that in MCF10A cells in MCF7 and MDA-MB-231 cells, respectively; therefore, the quantitative analysis indicated that AC8 overexpression in breast cancer cells is significantly greater than that of Orai1. Previous studies revealed a functional relationship between Orai1 and AC8 [19,21]; hence, we next explored the interaction between both proteins in the non-tumoral and tumoral breast cell lines by co-immunoprecipitation of cell lysates with anti-Orai1 antibody, followed by Western blotting with anti-AC8 antibody. The experiments were performed in resting cells as this interaction was previously shown to be constitutive [19].…”
Section: Expression and Interaction Of Orai1α And Ac8 In Non-tumoral mentioning
confidence: 99%
“…AC8 was reported to bind to an N-terminal sequence of Orai1 located between amino acids 26 and 34, which contains three serines (27, 30, and 34) [23]. This sequence is only present in the mammalian-specific full-length Orai1α variant and is absent in the short Orai1 variant, Orai1β [18]; thus, AC8 was reported to interact solely with Orai1α [21]. We assessed the expression of Orai1α and Orai1β in the three breast derived cell lines.…”
Section: Expression and Interaction Of Orai1α And Ac8 In Non-tumoral mentioning
confidence: 99%
See 1 more Smart Citation